Area per player in small-sided games to estimate the external load in elite youth soccer players - de Dios-Álvarez, V.; Padrón-Cabo, A.; Alkain-Villa, P.; Rey, E.; Castellano, J. (Journal of Human Kinetics, 2025)
Small-sided games (SSGs) refer to game formats where there are variations in the pitch size, the number of players, and rules as compared to official soccer matches. The purpose of this study was to assess the relationship between GPS-derived external loads and the SSGs` area per player (ApP) in elite youth soccer players to identify whether the ApP influenced GPS-derived external load measures to estimate external load variables from SSGs with different densities (i.e., ApP100: the ApP <150 m2·player-1; ApP200: the ApP ranged from 151 to 250; ApP300: the ApP > 251 m2·player-1). A cumulative count of 978 individual observations was undertaken, encompassing 15 diverse SSG configurations. The results showed moderate and large correlations between the ApP and external load measures for both U19 and U16 soccer players. The ApP300 induced higher locomotor activities than the ApP100 and the ApP200. However, the ApP100 showed higher mechanical (accelerations and decelerations) values compared to ApP200 and ApP300 conditions for both age groups. It was found that an ApP of less than 150 m2·player-1 in SSGs did not stimulate enough high-speed distance relative (HSDR), very high-speed distance relative (VHSDR) and sprint distance relative (SDR) compared to official matches in youth soccer players. However, the same ApP overestimated mechanical variables such as total high accelerations and decelerations relative to time (THACCR and THDECR, respectively). The findings of this study have the potential to facilitate the effective management of training loads tailored to specific fitness components of players.